Prognostic Factors and Adjuvant Treatments for Surgically Treated Cancers of the Biliary Tract: A Multicentre Study of the Anatolian Society of Medical Oncology (ASMO) - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Background: Biliary tract cancers are rare, and surgical resection is the standard treatment at early stages. However, reports on the benefits of adjuvant treatment following surgical resection are conflicting. This study aimed to evaluate the factors affecting survival and adjuvant treatments in patients with surgically treated biliary tract cancers. Materials and Methods: Patient clinical features, adjuvant treatments, and efficacy and prognostic factor data were evaluated. Survival analyses were performed using SPSS 15.0. Results: The median overall survival was 30.7 months (95% confidence interval [CI], 18.4-42.9 months). Median survival was 19 months (95% CI, 6-33) for patients treated with fluorouracil based chemotherapy and 53 months (95% CI, 33.2-78.8) with gemcitabine based chemotherapy (p=0.033). On univariate analysis, poor prognostic factors for survival were galbladder localization, perineural invasion, hepatic invasion, a lack of adjuvant chemoradiotherapy treatment, and a lack of lymph node dissection. On multivariate analysis, perineural invasion was a poor prognostic factor (p=0.008). Conclusions: Biliary tract cancers generally have poor prognoses. The main factors affecting survival are tumour localization, perineural invasion, hepatic invasion, adjuvant chemoradiotherapy, and lymph node dissection. Gemcitabine-based adjuvant chemotherapy is more effective than 5-fluorouracil-based chemotherapy.
Keywords: Biliary tract cancer; adjuvant chemotherapy; adjuvant chemoradiotherapy; prognostic factors; INTRAHEPATIC CHOLANGIOCARCINOMA PATIENTS; LYMPH-NODE RATIO; HILAR CHOLANGIOCARCINOMA; GALLBLADDER CANCER; PERINEURAL INVASION; CURATIVE SURGERY; SURVIVAL RATE; CARCINOMA; RESECTION; CHEMOTHERAPY